(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The subject of this research is the use of a HAPF to build up power quality during EAF operations in steel production. The HAPF system accomplishes well through simulation and experimental validation, and hence, shows an enviable performance in leveling power quality. Simulation shows that THD become one fifth of the original, which is 15%. Thus, practical wave shaping method is validated. They do not only protect the machines against current surges or overloads but also ensure voltage deviations are limited to ±2V under normal operation and even free up to ±3V over the load conditions to demonstrate the strength of voltage regulation capabilities. HAPF ensures the effective improvement in power factor of 0.85 lagging leading to0.98 leading during normal condition and 0.80 lagging to 0.95 leading under overload condition. Theory matches experimental results emphasizing the possibility of HAPF’s actualization and efficiency on the real-world production line. This study facilitates the diffusion of green technologies in the industry, thus, may cause an improvement in energy efficiency, operating stability of power provision and environmental impacts.